Enhencement of photo induced absorption of P3HT : PCBM by employing distributed Bragg reflector as the back reflector - Wang, Enze (2014)
Polymer photovoltaic devices have been intensively studied during the last 30 years [1]. In opposition with their inorganic counterpart, photoactive conjugated polymers possess extremely higher absorption coefficient allowing thin film being low cost devices. On the other hand, these materials are characterized by low charge mobility and high charge recombination rates which does not allow high power conversion efficiency. The research in this thesis mainly focused on the design and fabrication of polymer distributed Bragg reflectors (DBRs) [2] and their use as back reflector in polymer photovoltaic active layers. The effect of the mirror was investigated by photo induced absorption (PIA) of phenyl-C61-butyric acid methyl ester : poly(3-hexylthiophene (P3HT:PCBM) blend coupled with opportunely tuned DBR. Dielectric mirrors were prepared by spin coating of polymer solution. A matlab program was developed based on transfer matrix method to provide modeling of the DBR. PIA measurements show the enhancement of photo induced absorption by applying polymer DBR as the back reflector.